The Effectiveness of Ops-English Programme in Enhancing ESL Students’ Attitudes and Speaking Ability - Omar, Nurul Shuhada; Pek, Lim Seong; Mee, Rita Wong Mee (Selangor Humaniora Review, 2019)
This academic exercise aims to investigate the effectiveness of using the OPS-English programme to enhance ESL students’ speaking skills and attitudes. A total of thirty students in Form Two are randomly selected as subjects for collecting the data. Experimental design is used in this study to suit the need of the research done. The experiment of the OPS-English programme was conducted over three months. First, students’ achievement was analysed using a T-test based on the value of T=0.001. This study showed a significant scores difference in the pre-speaking test result after the students are treated with the OPS-English programme before the post-speaking test result. Besides, a Five-point Likert-scale questionnaire was administered to the respondents at the end of the course to identify their attitudes towards using the OPS-English programme in English classes. Finally, the data were analysed using percentages. The findings showed the students’ neutrality in speaking skills and attitudes after the OPS-English programme is introduced.